Sinergi Program Kebersihan dan Penanaman Pohon Mangga dalam Mewujudkan Lingkungan yang Sehat dan Berkelanjutan - Hermawan, Gilang Fawwaz Agnan (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity was carried out due to environmental issues, particularly the low awareness of cleanliness among the campus community and the limited green open space on the Sunan Giri University Surabaya campus. To address these issues, a combined approach was taken by integrating the environmental cleanup program with the planting of mango trees as a strategic step towards creating a healthier environment. The method used was Participatory Action Research (PAR), which actively involved students, lecturers, and campus staff in all stages of the process, including problem identification, planning, implementation, and evaluation. The results of the activities included a campus cleanup campaign and the planting of mango tree seedlings in designated locations. The results showed an increase in campus cleanliness, an increase in green areas, and increased awareness and involvement of participants in maintaining cleanliness and environmental sustainability. In addition to the physical benefits of a cleaner and greener campus, the activities also fostered values ​​such as teamwork, social responsibility, and environmental awareness among the campus community. Therefore, the combination of environmental cleanup and mango tree planting proved to be an effective participatory community service model that supports campus environmental sustainability.